The role of the solid-solution interface in the dissolution of benzoic acid. (17th February 2015) - Qiu, Yang; Li, Xianwen; Li, Gaoming; Zhou, Yaling; Qiu, Yishen
Abstract: An experiment using holographic interferometry shows that the evolution of the concentration profile produced by the dissolution of a benzoic acid powder compact cannot be satisfactorily described by the traditional treatments of assuming fast solubility equilibrium at the solid surface or equating dissolution rate with the diffusion flux at the boundary. A physical model was developed which incorporates the solid-solution interface into the kinetic description of the dissolution process. This leads to a boundary condition in which the time-dependence of boundary concentration follows an exponential function. The resulting solution to the diffusion equation shows good agreement with experimental data. Highlights: Holographic interferometry was used to monitor the dissolution of benzoic acid. Limitations of existing dissolution theories in describing our results were shown. A physical model involving the solid-solution interface was developed. This model yields a new boundary condition which describes our results well.